"GIVE ME CHILDREN OR ELSE I DIE" : A MATERNIDADE COMO NOVUM NA FICÇÃO CIENTÍFICA THE HANDMAID`S TALE (1985) DE MARGARET ATWOOD - Camargo, Mabiana (2015)
The Handmaid`s Tale (1985), a novel by the Canadian author Margaret Atwood, allows important reflections on the representation of motherhood as a multifaceted social, cultural and political process. In Atwood`s narrative, motherhood is presented frighteningly through the perspective of a handmaid who is obliged to procreate for the governing elite in a world where most women are infertile. Considering The Handmaid`s Tale also as a work which belongs to the literary mode science fiction (SF), this thesis aims to analyze it from the characteristics of SF and observe how certain categories operate in the novel, for example, the novum, which is the conducting thread of the plot. Thus, it is considered as an assumption that motherhood is the novum in the novel and surrounding it, other themes operate, such as totalitarianism, patriarchy and feminisms. Nevertheless, through the discussion of motherhood it is concluded that there are postmodern impulses in this work as well. To accomplish this discussion, Chapters I, entitled "Science fiction, motherhood: theoretical aspects" talks about the literary mode SF and its corresponding features, approaching its (in)definitions based on theoretical texts by Isaac Asimov, James Gunn, Paul Kincaid, and Samuel Delany and it also brings into light a theoretical review on motherhood, which presents itself as a complex and contradictory process. In this second part the authors who guide the discussion are Simone de Beauvoir, Elisabeth Badinter, Gilles Lipovetsky, Sharon Hays, Nancy Chodorow, and Sara Ruddick. Chapter II, called "The Handmaid`s Tale: motherhood as the novum", consists on the analysis of the The Handmaid`s Tale, observing how the issues of motherhood as the novum are developed and also how they raise other themes addressed by Atwood. Chapter III, called "Final remarks", presents the final ideas, synthesizing and concluding what has been presented in the previous chapters.